2019
DOI: 10.1177/0003319719892160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Relationship Between Inflammatory Markers and Contrast-Induced Nephropathy in Patients With Acute Coronary Syndrome After Coronary Angiography

Abstract: Contrast-induced nephropathy (CIN) is one of the most important complications after invasive cardiovascular procedures. The neutrophil-to-lymphocyte ratio (NLR), mean platelet volume-to-lymphocyte ratio (MPVLR), and platelet-to-lymphocyte ratio (PLR) may be markers of the risk of CIN. We aimed to investigate the association of these indices with the development of CIN in patients with ST-elevation myocardial infarction and non-ST-elevation-acute coronary syndrome who underwent percutaneous coronary interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
(51 reference statements)
1
29
0
Order By: Relevance
“…Inflammatory factors cause atherosclerotic plaques to develop and become unstable, leading to thrombosis and resulting in obstruction of the coronary arteries (29). Studies have indicated that ACS is an inflammation-mediated atherosclerotic disease and that inflammation and immune responses have an important role at all stages of atherosclerosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory factors cause atherosclerotic plaques to develop and become unstable, leading to thrombosis and resulting in obstruction of the coronary arteries (29). Studies have indicated that ACS is an inflammation-mediated atherosclerotic disease and that inflammation and immune responses have an important role at all stages of atherosclerosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the presence of inflammatory elements has also been set as a feature for the population at high risk of CIN. Several studies have reported that the presence of active inflammatory processes biomarkers in patients with CVD may attribute its high-risk to developing CIN after CM exposure [30,31,[91][92][93][94] .…”
Section: Cin Pathophysiology In the Context Of Cvdmentioning
confidence: 99%
“…7 Zorlu and Koseoglu. 3 did not report the LMR. However, this may be investigated in future studies.…”
mentioning
confidence: 99%